PERAN HAK KEKAYAAN INTELEKTUAL KOMUNAL DALAM PENGEMBANGAN EKSPRESI BUDAYA PACU JALUR DI PROVINSI RIAU - Muhammad Syafi’i (Fakultas Hukum Universitas Islam Indonesia, 2023)
This study analyse the role of Intellectual Property Rights to develop cultural expression “Pacu Jalur” from Riau province. It aims to find out how the current legal system protect and utilize communal rights so that it can be preserved. Normative research is applied as the methodology where secondary data such as laws, regulations, and relevant study are present. Analysis are done through quantitative and qualitative description. This study obtained that Pacu Jalur is part of Communal Rights that have to be protected and developed to be an identity of Taluk Kuantan Regency in Riau Province. Such right are not fully implemented and it is advised to be improved so that economic benefit could be realized.